Autonomy of experience: time, space, path and place as blended artistic methodology in MAP, an online, interactive poetry experience. Issue 2 (4th May 2022) - Mueller, Caroline
ABSTRACT: This article will discuss M A P, an interactive poetic experience facilitated on the popular media sharing application Instagram, which was developed as a research-based, cross-course collaboration. The artistic methodology applied during M A P was developed during the global pandemic of COVID-19 and was created with, and inspired by the use of blended learning approaches. Acknowledging and addressing the social disconnect and technological hyper-connect during the pandemic, M A P can be understood as a practice-as-research experimentation that investigates how digital technologies might be repurposed in blended artistic practice to allow for a more reflective and embodied experience of ourselves and others in time and place. The makers of M A P advocate the facilitation of autonomous choice-making, particularly in relation to the use of time, space, path and pace, as well as the application of slow technology and slow design considerations to develop abstract story-telling and relational sense-making through the merging of online and real-world activities. M A P can be accessed via Instagram on @map_game_start or via https://www.themapexperience.com .